The Role of Environmental Attitude as Mediator Between Perceived Sustainability Policy and Spiritual Well-Being Toward Pro-Environmental Behavior: [Peran Environmental Attitude Sebagai Mediator Perceived Sustainability Policy dan Spiritual Well-Being Atas Pro-Environmental Behavior] - Soeharso, Silverius Y.; Ningtyas, Lisa Dwi; Sundari, Resy (ANIMA Indonesian Psychological Journal, 2023)
This study aims to ascertain the role of the environmental attitude (EA) variable as a moderator in the relationship between perceived sustainability policy (PSP) and spiritual well-being (SpWB) on pro-environmental behavior (PEB). The sampling technique utilized was convenience sampling, and 127 respondents were selected, consisting of lecturers and education staffs at several universities in DKI Jakarta. The measuring instruments utilized are the Pro-Environmental Behavior (PEB) Scale, Environmental Attitude (EA) Scale, Perceived Sustainability Policy (PSP) Scale, and Spiritual Well-Being (SpWB) Scale; with Structural Equation Model (SEM) as the data analysis. The conclusion is that the relationship model consisting of the variables pro-environmental behavior (PEB), environmental attitude (EA), spiritual well-being (SpWB), and perceived sustainability policy (PSP) "fits" and/or significant with the study data, although the relationship between several variables is not significant. Environmental attitude (EA) in this study was not proven to be a mediator between spiritual well-being (SpWB) and perceived sustainability policy (PSP) on pro-environmental behavior (PEB). Insignificant results may be caused by the small size of the samples. University management is suggested to implement pro-environmental policies to create a green and sustainable campus environment. Studi ini bertujuan untuk mengkaji peran variabel environmental attitude (EA) sebagai moderator pada hubungan antara perceived sustainability policy (PSP) dan spiritual well-being (SpWB) terhadap pro-environmental behavior (PEB). Teknik sampling yang digunakan adalah convenience sampling, dan dipilih 127 responden yang terdiri dari dosen dan tenaga kependidikan di sejumlah universitas di DKI Jakarta. Alat ukur yang digunakan adalah Pro-Environmental Behavior (PEB) Scale, Environmental Attitude (EA) Scale, Perceived Sustainability Policy (PSP) Scale, dan Spiritual Well-Being (SpWB) Scale; dengan Structural Equation Model (SEM) sebagai analisis data. Hasil studi menyimpulkan bahwa model hubungan struktural yang terdiri dari variabel pro-environmental behavior (PEB), environmental attitude (EA), spiritual well-being (SpWB), dan perceived sustainability policy (PSP) “fit” dan/atau signifikan dengan data studi, walaupun hubungan beberapa variabel tidak signifikan. Environmental attitude (EA) pada studi ini tidak terbukti dapat menjadi mediator antara spiritual well-being (SpWB) maupun perceived sustainability policy (PSP) terhadap pro-environmental behavior (PEB). Hasil yang tidak signifikan dapat disebabkan oleh ukuran sampel yang kecil. Manajemen perguruan tinggi disarankan untuk memberlakukan kebijakan pro-lingkungan tersebut, dalam rangka menciptakan lingkungan kampus hijau dan berkelanjutan.